2016
DOI: 10.1111/gtc.12383
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin PpiB is involved in motility and biofilm formation via its functional association with certain proteins

Abstract: PpiB belongs to the superfamily of peptidyl-prolyl cis/trans isomerases (PPIases, EC: 5.2.1.8), which catalyze the rate-limiting protein folding step at peptidyl-prolyl bonds and control several biological processes. In this study, we show that PpiB acts as a negative effector of motility and biofilm formation ability of Escherichia coli. We identify multicopy suppressors of each DppiB phenotype among putative PpiB prey proteins which upon deletion are often characterized by analogous phenotypes. Many putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 123 publications
(224 reference statements)
2
34
0
Order By: Relevance
“…Previously, we have shown that PpiB modulates various bacterial behaviors such as swimming and swarming motility and biofilm formation ability in a negative way (Skagia et al . ). In many reported cases, elimination of the prolyl isomerase activity of a PPIase had no or little impact on protein interactions and/or chaperoning activities, indicating that PPIases can also act as chaperones or accessory components of multiprotein complexes (Göthel & Marahiel ; Chakraborty et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, we have shown that PpiB modulates various bacterial behaviors such as swimming and swarming motility and biofilm formation ability in a negative way (Skagia et al . ). In many reported cases, elimination of the prolyl isomerase activity of a PPIase had no or little impact on protein interactions and/or chaperoning activities, indicating that PPIases can also act as chaperones or accessory components of multiprotein complexes (Göthel & Marahiel ; Chakraborty et al .…”
Section: Resultsmentioning
confidence: 97%
“…The previously described primers carry restriction sites for ligation to the pCDFDuet‐1 expression vector (Skagia et al . ). The fragments excised from amplified sequences were cloned between the corresponding sites of pCDFDuet‐1, resulting in F99A His ‐Prey S .pCDFDuet‐1.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The swarming motility plates were prepared with 0.5% Fluka agar, 1% Bacto-Tryptone, 0.5% yeast extract, 1% NaCl, and 0.5% D-(+)-glucose. Biofilm formation and quantification assays were performed as previously described [O'Toole and Kolter, 1998;Skagia et al, 2016].…”
Section: E Coli Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
“…Previously, we have shown that the cytoplasmic cyclophilin PpiB has a negative effect on swimming and swarming motility and the biofilm formation ability of E. coli in a way that employs the prolyl isomerase activity of the enzyme only in the 2 latter cases [Skagia et al, 2016;Skagia et al, 2017]. Since the periplasmic cyclophilin PpiA is regulated by the Cpx 2-component system which senses also adhesion [Dorel et al, 2006;Vogt and Raivio, 2012], we hypothesized that PpiA might be involved in biofilm formation as well.…”
mentioning
confidence: 99%